PENGELOLAAN WAKAF UANG: USULAN SKEMA PEMBIAYAAN USAHA MIKRO, KECIL DAN MENENGAH - Sri Noerhidajati; Fahruroji Fahruroji (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
Waqf plays an important role in improving the welfare of the community. Commonly known waqf is in the form of land or buildings. In its development, the idea of waqf emerged in the form of money so that it can be used more productively. Waqf assets can be invested to finance certain projects that are profitable and comply with sharia principles. In order for the principal value of the waqf to not decrease, the investment must have a low risk. Utilization of cash waqf for productive activities includes capital financing for micro, small and medium enterprises (MSMEs). Usually, financing for MSMEs has been carried out by means of a qard contract. Financing with a qard contract has the risk of unreturned waqf principal. This study aims to propose MSME financing scheme originating from cash waqf funds with the supply chain financing (SCF) model. This scheme has a relatively low risk, because the financing is provided on the basis of MSME bills to business partners.